The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1471-0528.12717
|View full text |Cite
|
Sign up to set email alerts
|

Uterine sutures at prior caesarean section and placenta accreta in subsequent pregnancy: a case–control study

Abstract: Objective To clarify the effects of uterine myometrial suture techniques at prior caesarean section on the incidence of pathologically diagnosed placenta accreta in placenta praevia with prior caesarean section (PPPC).Design Case-control study.Setting Eleven tertiary referral hospitals in central Japan.Population A total of 98 cases of placenta praevia, a history of one or more prior caesarean sections, and a history of uterine transverse incision and usage of only absorbable thread for myometrial sutures at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…10 The conclusion was that there was no significant difference in interpregnancy interval and risk of AIP; however, these women were not matched by location of placenta and it is therefore difficult to interpret these results. 10 Another study by Wax et al, which was underpowered, sought to determine cesarean to conception interval and the effect on development of abnormally adherent placenta. 11 They concluded that cesarean to conception mean intervals are shorter in women with abnormally adherent placentas (35 months) vs controls (48 months); however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…10 The conclusion was that there was no significant difference in interpregnancy interval and risk of AIP; however, these women were not matched by location of placenta and it is therefore difficult to interpret these results. 10 Another study by Wax et al, which was underpowered, sought to determine cesarean to conception interval and the effect on development of abnormally adherent placenta. 11 They concluded that cesarean to conception mean intervals are shorter in women with abnormally adherent placentas (35 months) vs controls (48 months); however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…2 The explanation by Sumigama et al that 'it is the incomplete healing and insufficiency of the endometrium that may allow villous invasion, and once myometrium has been invaded, further invasion cannot be prevented' seems unsound. 1 The endometrium does not heal end-to-end or form a bond (over a period of up to 12 months?). 1 Moreover, the trophoblastic invasion of myometrium occurs in all pregnancies, not just with placenta accreta.…”
Section: Sirmentioning
confidence: 99%
“…1 The endometrium does not heal end-to-end or form a bond (over a period of up to 12 months?). 1 Moreover, the trophoblastic invasion of myometrium occurs in all pregnancies, not just with placenta accreta. Nonetheless, their article does focus our attention to thinking about the effect of the surgical techniques of uterine incision closure on the subsequent scar integrity.…”
Section: Sirmentioning
confidence: 99%
“…Several risk factors are established such as previous uterine surgery, placenta previa, multiparity, advanced maternal age, previous endometritis, and so on [3][4][5]. When one previous cesarean section was complicated with placenta previa, the incidence rate of placenta accreta was reported to be 11-37%, showing further increases with an increased number of prior cesarean deliveries (over 60% in previa with 3 or more prior cesarean deliveries) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%